Hadronic resonances with exotic electric charge - De Conto, G. [UNESP]; Pleitez, V. [UNESP] (Amer Physical Soc, 2017)
We classify the meson and baryon long lived resonances that may exist if quarks with electric charge 5/3 and -4/3 (in units of vertical bar e vertical bar) predicted by some 3-3-1 models do exist. Some of these exotic resonances have the usual electric charges or +/-(3,4,5), and the lightest ones decaying only into leptons plus known resonances. We propose another heavy SU(3)(H) global symmetry under which hadrons involving only exotic quarks can be constructed.